ISLAMIC EDUCATION TEACHERS' EFFORTS IN INSTILLING ISLAMIC VALUES THROUGH PROPHET AND COMPANION STORIES IN THE CLASSROOM - Rohman, Mohammad Zuhal Fathur; Chotib, Moch.; Muhith, Abdul (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Instilling Islamic values in students is one of the main objectives of Islamic religious education (PAI). Stories about the Prophet and his companions are one of the effective methods to convey these values. This study aims to examine how PAI teachers use stories of Prophets and Companions as learning media in the classroom, as well as their impact on students' understanding and behavior. This research uses a qualitative approach with a case study method in one of the elementary schools in Indonesia. Data were obtained through observation, interviews, and document analysis. The results show that the use of Prophet and Companion stories can increase students' interest in learning religion and help them understand and internalize Islamic values. This article suggests the development of a story-based learning module to improve the effectiveness of PAI learning.